Polymer-based composite solid electrolyte membrane, preparation method and lithium battery
By using a multi-layered polymer-based composite solid electrolyte membrane in lithium-ion batteries, the problem of poor compatibility between solid electrolyte and negative electrode in lithium-ion batteries is solved, and the high capacity and cycling performance of the battery are improved.
Patent Information
- Application Number
- CN202510026402.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-02-01
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-28
AI Technical Summary
In existing lithium-ion batteries, the compatibility between solid electrolyte and negative electrode is poor, resulting in large-scale use.
A polymer-based composite solid electrolyte membrane is used, which consists of multi-layer halide solid electrolyte and polymer solid electrolyte. By reducing the mass ratio of halide solid electrolyte to polymer solid electrolyte layer by layer, the compatibility and performance of the battery are improved.
It has achieved high capacity and cycle performance improvements in lithium-ion batteries, and has good high voltage resistance and negative electrode compatibility.
Smart Images

Figure BDA0005232846460000351 
Figure BDA0005232846460000361
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of lithium-ion batteries, and specifically relates to a polymer-based composite halide solid electrolyte membrane and a preparation method thereof; it also relates to a lithium battery prepared using the composite halide solid electrolyte membrane. Background Art
[0002] As a green energy source, lithium-ion batteries have received widespread attention. Currently, most of the widely used lithium-ion batteries use electrolytes as the transmission medium for lithium ions. Although they have good capacity performance, their safety performance is poor, which is not conducive to their large-scale development. Researchers have tried to replace electrolytes with solid electrolytes as the transmission medium for lithium ions inside batteries. Existing solid electrolytes mainly include oxide solid electrolytes, halide solid electrolytes, sulfide solid electrolytes and polymer solid electrolytes. However, these solid electrolytes still face huge challenges in practical applications. For example, oxide solid electrolytes have high hardness and poor processing performance, so the interface impedance between them and electrode materials is large; there are side reactions between sulfide solid electrolytes and electrode materials, the voltage window is narrow, and they are sensitive and unstable to air / humidity. However, most of the above disadvantages do not exist in halide solid electrolytes.
[0003] Halide solid electrolytes have the advantages of high lithium ion mobility, strong deformability, and low Young's modulus, and can be used to prepare soft and highly conductive electrolyte membranes. Both experiments and theoretical calculations have shown that halide solid electrolytes have a high electrochemical window and can match high-voltage positive electrodes, which is not available in other inorganic solid electrolytes, such as oxide solid electrolytes and sulfide solid electrolytes. In addition, the synthesis process of halide solid electrolytes is simple and does not require high-temperature sintering, reducing energy consumption. However, the poor compatibility of halide solid electrolytes with negative electrodes prevents their large-scale use. Summary of the invention
[0004] Based on this, in order to solve the above problems, the present application provides a polymer-based composite solid electrolyte membrane and a preparation method thereof, and a lithium battery to solve the above technical problems.
[0005] The first aspect of the present application provides a polymer-based composite solid electrolyte membrane, the composite solid electrolyte membrane comprising N solid electrolyte layers, each solid electrolyte layer comprising a halide solid electrolyte and a polymer solid electrolyte, and the outermost solid electrolyte layer is the first solid electrolyte layer and the Nth solid electrolyte layer, then the following conditions are satisfied:
[0006] The mass proportion of the halide solid electrolyte in the first solid electrolyte layer is greater than the mass proportion of the halide solid electrolyte in the Nth solid electrolyte layer;
[0007] The types of the halide solid electrolytes in different solid electrolyte layers may be the same or different.
[0008] In some embodiments, N solid electrolyte layers are stacked, and the mass ratio of the halide solid electrolyte to the polymer solid electrolyte in each solid electrolyte layer gradually decreases from the first solid electrolyte layer to the Nth solid electrolyte layer.
[0009] In some embodiments, in each solid electrolyte layer, the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is (90:10) to (5:95).
[0010] In some embodiments, in the first solid electrolyte layer, the mass percentage of the halide solid electrolyte is 50 wt % to 90 wt %.
[0011] In some preferred embodiments, in the Nth solid electrolyte layer, the mass proportion of the polymer solid electrolyte is 70 wt % to 95 wt %.
[0012] In some embodiments, the halide solid electrolyte includes Li a M b X 6 , wherein M includes one or more combinations of Zr, Hf, In, Sc, Y, La, Ce, Pr, Nb, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; X includes a halogen element or a combination of a halogen element and an O element or a combination of a halogen element and an S element, and the halogen element includes one or more combinations of F, Cl, Br, and I; a>0, b>0, and a+b=6.
[0013] In some embodiments, the polymer solid electrolyte includes a first polymer solid electrolyte, and the first polymer solid electrolyte includes one or more of PEO, PVDF, PMMA, PAN, PVC, PA, PEGDA, and PTMC.
[0014] In some preferred embodiments, the first polymer solid electrolyte includes PEO.
[0015] In some embodiments, the halide solid electrolytes in the N solid electrolyte layers are the same, and the polymer solid electrolytes are the same.
[0016] In some embodiments, the polymer solid electrolyte further includes a lithium salt.
[0017] In some embodiments, the lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, lithium tetrachloroaluminate, lithium iodide, lithium bromide, lithium thiocyanate, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium tetraphenylborate, lithium bis(oxalate)borate, lithium tetrafluorooxalatophosphate, lithium nitrate, lithium hexafluoroarsenate, lithium trifluoromethanesulfonate, lithium bis(trifluorosulfonyl)imide ... bis(trifluorosulfonyl)imide, lithium bis(trifluorosulfonyl)imide, lithium bis(trifluorosulfonyl)imide, lithium bis(trifluorosulfonyl)imide, lithium bis(trifluorosulfonyl)imide, lithium bis(trifluorosulfonyl
[0018] In some embodiments, in the polymer solid electrolyte, the mass ratio of the lithium salt to the first polymer solid electrolyte is (5:95) to (60:40).
[0019] The second aspect of the present application provides a method for preparing a composite solid electrolyte membrane as in the first aspect, characterized in that it comprises the following steps:
[0020] S1. Prepare separate solid electrolyte layers: weigh raw materials, mix and press to form solid electrolyte layers;
[0021] S2. Composite: Roll-compound the N solid electrolyte layers prepared in step S1.
[0022] In a third aspect, the present application provides a lithium battery, comprising a positive electrode, a negative electrode, and a polymer-based composite solid electrolyte membrane as in the first aspect disposed between the positive and negative electrodes;
[0023] The first solid electrolyte layer is in contact with the positive electrode, and the Nth solid electrolyte layer is in contact with the negative electrode.
[0024] The positive electrode includes a positive electrode active material, and the positive electrode active material includes a high voltage positive electrode material.
[0025] The present application prepares a polymer-based composite solid electrolyte membrane composed of several solid electrolyte layers with different mass proportions of halide solid electrolytes, which has good high-voltage resistance, good negative electrode compatibility, and good ionic conductivity. From the first solid electrolyte layer to the Nth solid electrolyte layer, the mass ratio of the halide solid electrolyte to the polymer solid electrolyte in each solid electrolyte layer gradually decreases. When applied to a solid-state battery, the first solid electrolyte is contacted and coordinated with the positive electrode, and the Nth solid electrolyte layer is contacted and coordinated with the negative electrode, which can achieve excellent compatibility with the positive electrode and the negative electrode at the same time, which can effectively improve the capacity performance of the battery and the cycle performance of the battery. DETAILED DESCRIPTION
[0026] References to embodiments of the present application will now be provided in detail, one or more embodiments of which are described below. Each embodiment is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.
[0027] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.
[0028] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0029] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0030] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 100-150nm means that the units of the left endpoint "100" and the right endpoint "150" are both nm (nanometers).
[0031] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0032] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0033] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0034] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0035] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0036] The first aspect of the present application provides a polymer-based composite solid electrolyte membrane, comprising N solid electrolyte layers, each of which comprises a halide solid electrolyte and a polymer solid electrolyte, and the outermost solid electrolyte layer is the first solid electrolyte layer and the Nth solid electrolyte layer, then:
[0037] The mass proportion of the halide solid electrolyte in the first solid electrolyte layer is greater than the mass proportion of the halide solid electrolyte in the Nth solid electrolyte layer;
[0038] The types of the halide solid electrolytes in different solid electrolyte layers may be the same or different.
[0039] In some embodiments, the mass proportion of the polymer solid electrolyte in the Nth solid electrolyte layer is greater than the mass proportion of the polymer solid electrolyte in other solid electrolyte layers.
[0040] It is understandable that in order to improve the energy density of the battery, the positive electrode mostly uses high-voltage positive electrode active materials, so the electrolyte membrane needs to have good high-voltage resistance to prevent the electrolyte membrane from being oxidized and decomposed by the positive electrode during contact with the positive electrode, causing the battery's cycle performance to deteriorate. In this application, the solid electrolyte layer includes a halide solid electrolyte and a polymer solid electrolyte, and the two work synergistically to effectively improve the high-voltage resistance of the composite electrolyte membrane. At the same time, since each solid electrolyte layer includes a halide solid electrolyte and a polymer solid electrolyte, compared to a composite layer structure composed of a single halide solid electrolyte layer and a single polymer solid electrolyte layer, the composite electrolyte membrane of the present application does not have additional interface problems between solid electrolyte layers, effectively reducing the internal resistance of the battery and improving the capacity performance of the battery.
[0041] In some embodiments, N solid electrolyte layers are stacked and arranged, and the mass ratio of the halide solid electrolyte to the polymer solid electrolyte in each solid electrolyte layer gradually decreases from the first solid electrolyte layer to the Nth solid electrolyte layer. The mass of the polymer solid electrolyte in the Nth solid electrolyte layer accounts for the largest proportion. The gradient distribution of halide powder and polymer solid electrolyte can solve the interface effect of the direct composite existence of the halide membrane and the polymer membrane, and the ionic conductivity will no longer be limited to the halide electrolyte membrane or the polymer electrolyte membrane. At the same time, in the first solid electrolyte layer, the halide electrolyte content is high. When used in a solid-state battery, the first solid electrolyte layer is used in contact with the positive electrode. The good high-voltage resistance of the halide electrolyte can make the battery system adapt to a higher voltage positive electrode, thereby improving the overall energy density of the battery. In addition, the polymer electrolyte content in the Nth solid electrolyte layer increases. When used in a solid-state battery, it is used in conjunction with the negative electrode to effectively improve the problem of poor compatibility between the halide electrolyte membrane system and the negative electrode.
[0042] In some preferred embodiments, the polymer-based composite solid electrolyte membrane includes 2 to 6 layers of solid electrolyte layers, that is, the preferred value of N is 2 to 6. When the number of solid electrolyte layers is greater than 6, the film-making process will be complicated and the thickness of the electrolyte after composite will be uneven. When the polymer-based composite solid electrolyte membrane includes only one layer of solid electrolyte, the electrolyte powder contains both halide electrolyte and polymer electrolyte, and there will be polymers that are not resistant to high voltage directly in contact with the high voltage positive electrode, and halide electrolytes that are not resistant to reduction directly in contact with the negative electrode, resulting in increased side reactions in the battery and decreased cycle performance. Preferably, the polymer-based composite solid electrolyte membrane includes 3 to 4 layers of solid electrolyte layers. The advantage of this arrangement is that when the number of layers of the solid electrolyte layer is 2, there is a large difference in the mass proportion of halides in the first solid electrolyte layer and the Nth solid electrolyte layer, which causes the ionic conductivity of the polymer-based composite solid electrolyte membrane to be greatly affected. When the mass proportion of halides is small, it is easy to have a low ionic conductivity of the polymer-based composite solid electrolyte membrane, or the compatibility with the positive and negative electrodes is not significantly improved.
[0043] In some preferred embodiments, from the first solid electrolyte layer to the Nth solid electrolyte layer, in each solid electrolyte layer, the mass proportion of the halide solid electrolyte gradually decreases, and the mass proportion of the polymer solid electrolyte gradually increases.
[0044] In some embodiments, the thickness of each solid electrolyte layer is 3 to 30 μm, including but not limited to 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, and 25 μm; preferably 5 to 25 μm.
[0045] In some embodiments, the thickness of each solid electrolyte layer is the same.
[0046] In some embodiments, the thickness of each solid electrolyte layer is different.
[0047] In some embodiments, in each solid electrolyte layer, the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is (90:10) to (5:95), including but not limited to 90:10, 85:15, 80:20, 75:25, 70:30, 60:40, 50:50, 40:60, 30:70, and 10:90.
[0048] In some embodiments, in the first solid electrolyte layer, the mass proportion of the halide solid electrolyte is 50 wt % to 90 wt %; preferably, 70 wt % to 90 wt %.
[0049] In some preferred embodiments, in the Nth solid electrolyte layer, the mass percentage of the polymer solid electrolyte is 70 wt % to 95 wt %.
[0050] It is understood that the halide solid electrolyte is a known electrolyte material, which is considered to have the advantages of both oxide solid electrolytes and sulfide solid electrolytes. In some embodiments, the halide solid electrolyte includes Li a M b X 6 , wherein M is a metal element, which can be a mixture of multiple metal elements, and the multiple metals can be of the same valence or different valence. Exemplarily, M includes one or more combinations of Zr, Hf, In, Sc, Y, La, Ce, Pr, Nb, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; X is a halogen element or a combination of a halogen element and an O element or a combination of a halogen element and an S element, and the halogen element includes one or more combinations of F, Cl, Br, and I; a>0, b>0, and a+b=6.
[0051] The present application does not specifically limit the type of halide solid electrolyte. Without violating the inventive concept of the present application, any known halide solid electrolyte can be used in the present application. This is only used as an illustrative example rather than a limitation on the scope of protection. The halide solid electrolyte can be Li 2 ZrCl 6 , Li 3 InCl 6 , Li 3 YC 6 , Li 3 ScCl 6 , Li 3 YC 3 Br 3 and their combinations.
[0052] Further, the particle size range of the halide solid electrolyte powder is 0.1 μm to 40 μm. Including but not limited to 0.1 μm, 0.2 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm and 40 μm. In some embodiments, the particle size range of the halide solid electrolyte powder is 3 μm to 30 μm. In some further embodiments, the particle size range of the halide solid electrolyte powder is 5 μm to 20 μm.
[0053] In some embodiments, the polymer solid electrolyte includes a first polymer solid electrolyte, and the first polymer solid electrolyte includes one or more of PEO (polyethylene oxide), PVDF (polyvinylidene fluoride), PMMA (polymethyl methacrylate), PAN (polyacrylonitrile), PVC (polyvinyl chloride), PA (polyimide), PEGDA (polyethylene glycol diacrylate), and PTMC (polytrimethylene carbonate). The first polymer solid electrolyte first plays the role of transmitting lithium ions, and secondly can effectively improve the problem of poor compatibility between the halide solid electrolyte and the negative electrode. The polymer electrolyte also has the characteristics of being soft and dense. It can fill the gaps between the halide powder particles during the preparation process of the halide electrolyte and the polymer electrolyte composite membrane, thereby improving the density of the electrolyte composite membrane and thereby improving the ionic conductivity.
[0054] In some preferred embodiments, the first polymer solid electrolyte includes PEO. PEO is a commonly used electrolyte. During the ion transport process, the breaking and reconstruction of the Li-O bond in PEO is used to make the electrolyte have lithium ion transport properties. In this process, no solvent or other initiator is required to make the electrolyte have lithium conductivity. Solvent-free and additive-free can greatly avoid the problem of incompatibility between halides and most solvents.
[0055] In some embodiments, the halide solid electrolytes in the N solid electrolyte layers are the same, and the polymer solid electrolytes are the same. It can be understood that the same here means that except for the different mass proportions, the rest are the same. The purpose of this setting is to further reduce the internal resistance of the polymer-based composite solid electrolyte membrane composed of the multilayer structure, which is conducive to the rapid conduction of lithium ions.
[0056] In some embodiments, the polymer solid electrolyte further includes a lithium salt. The lithium salt cooperates with the first polymer solid electrolyte to effectively prevent the problem of decreased ion conductivity caused by adding the polymer solid electrolyte to the halide solid electrolyte.
[0057] In some embodiments, the lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, lithium tetrachloroaluminate, lithium iodide, lithium bromide, lithium thiocyanate, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium tetraphenylborate, lithium bis(oxalate)borate, lithium tetrafluorooxalatophosphate, lithium nitrate, lithium hexafluoroarsenate, lithium trifluoromethanesulfonate, and lithium bis(fluorosulfonyl)imide.
[0058] In some embodiments, in the polymer solid electrolyte, the mass ratio of the lithium salt to the first polymer solid electrolyte is (5:95) to (60:40).
[0059] In some embodiments, the mass proportion of the lithium salt gradually increases from the first solid electrolyte layer to the Nth solid electrolyte layer.
[0060] In some embodiments, the increased amount of the lithium salt is proportional to the increased amount of the first polymer solid electrolyte.
[0061] In some embodiments, each solid electrolyte layer further includes a binder, and the mass proportion of the binder is less than 5%.
[0062] The binder is a fibrillating binder, that is, under the action of high shear force, the binder can be transformed from a granular state to a fibrous state. On the one hand, by setting the mass proportion of the binder and the morphology of the binder, it is possible to prevent the binder from coating the surface of the solid electrolyte particles, resulting in poor ion transmission between particles, thereby significantly reducing the ion conductivity of the solid electrolyte layer, and ultimately causing serious losses in the rate performance and capacity of the battery. On the other hand, it can also effectively avoid the problem of instability between the solid electrolyte and most solvents.
[0063] Exemplarily, the fiberizable binder includes polytetrafluoroethylene, a combination of polytetrafluoroethylene and one or more of polyvinylidene fluoride, polyvinylidene fluoride hexafluoropropylene, polypropylene, polyethylene, and polyimide.
[0064] The second aspect of the present application provides a method for preparing a composite solid electrolyte membrane as in the first aspect, characterized in that it comprises the following steps:
[0065] S1. Preparing a separate solid electrolyte layer: weighing raw materials, mixing, and pressing to form a solid electrolyte layer;
[0066] In some embodiments, in step S1, a halide solid electrolyte and a polymer solid electrolyte are weighed, wherein the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is (90:10) to (5:95).
[0067] In some embodiments, in step S1, a halide solid electrolyte, a first polymer solid electrolyte, and a lithium salt are weighed, wherein the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is (90:10) to (5:95), and in the polymer solid electrolyte, the mass ratio of the lithium salt to the first polymer solid electrolyte is (5:95) to (60:40).
[0068] In some embodiments, in step S1, a halide solid electrolyte, a first polymer solid electrolyte, a lithium salt and a binder are weighed, wherein the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is (90:10) to (5:95), the mass ratio of the lithium salt to the first polymer solid electrolyte is (5:95) to (60:40), and the mass proportion of the binder is <5%.
[0069] There is no particular limitation on the mixing method in this application. Without violating the inventive concept of this application, any known mixing method can be applied to this application, which is only used as an illustrative example, not a limitation on the scope of protection. In step S1 of preparing the first mixture, the halide solid electrolyte, polymer solid electrolyte, lithium salt and binder can be mixed by ball milling, air flow mixing or pulverizer. In some embodiments, the halide solid electrolyte powder, binder and lubricant are mixed by pulverizer.
[0070] After the mixing step, a fiberizing step is also included. It is understood that in some embodiments, the halide solid electrolyte, polymer solid electrolyte, lithium salt and binder can also be directly placed in a device that provides shear force, and fiberization is completed during continuous mixing. In other embodiments, the mixing process and the fiberizing process are completed in the same device. Exemplarily, the device is a high-speed shearing machine.
[0071] Under the action of shear force, the binder changes from powder to fiber and is evenly distributed between the particles of the halogen solid electrolyte, forming a binder-bridging solid electrolyte particle structure.
[0072] In the present application, a mixture of a halide solid electrolyte and a polymer solid electrolyte is calendered by a roller press and / or a flat plate extrusion and / or a mold pressing method to obtain a solid electrolyte membrane. In some embodiments, the second mixture is calendered by a pair of rollers.
[0073] Further, the pair of rollers includes a first roller member and a second roller member that are arranged opposite to each other, wherein the roller speeds of the first roller member and the second roller member may be the same or different.
[0074] Since the polymer solid electrolyte has a certain elasticity, during the rolling process, the polymer solid electrolyte moves between the halide solid electrolyte particles, which can effectively improve the density of the composite solid electrolyte membrane.
[0075] S2. Composite: Roll-compound the plurality of solid electrolyte layers prepared in step S1.
[0076] In some embodiments, step S20 is further included before step S2, stacking N solid electrolyte layers in ascending order of mass percentage of halide solid electrolyte.
[0077] In some embodiments, the porosity of the polymer-based composite solid electrolyte membrane is 0.05% to 40%.
[0078] In a third aspect, the present application provides a lithium battery, comprising a positive electrode, a negative electrode, and a polymer-based composite solid electrolyte membrane as in the first aspect disposed between the positive and negative electrodes;
[0079] The positive electrode comprises a positive electrode plate, a positive electrode tab is led out of the positive electrode plate, and the positive electrode plate comprises a positive electrode current collector and a positive electrode active electrode material layer formed on the current collector.
[0080] The positive electrode includes a positive electrode active material, and the positive electrode active material includes a high voltage positive electrode material; in the present application, "high voltage positive electrode material" refers to a material having a continuous oxidation decomposition potential U that satisfies U≥4.2V.
[0081] The positive electrode active material layer includes a positive electrode active material, which is a compound capable of reversibly inserting and extracting lithium. The positive electrode active material is a high voltage positive electrode material selected from LiCo 1~y M y O 2 、LiNi 1~y M y O 2 、LiMn 2~y M y O 4 and LiNi x Co y Mn z M 1~x~y~z O 2 At least one of the following, wherein M is selected from one or more of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V and Ti, and 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1.
[0082] In some embodiments, the mass proportion of the positive electrode active material contained in the positive electrode active material layer can be 50wt% to 97wt%, such as 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt%, 97wt%, etc., preferably 80wt% to 90wt%.
[0083] The positive electrode also includes a positive electrode binder, which is used to bind the positive electrode active material, the positive electrode conductive material, the positive electrode current collector and other components together. Specifically, the positive electrode binder includes a fiberized binder. Preferably, the fiberized binder includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride hexafluoropropylene, polypropylene, polyethylene, and polyimide.
[0084] The mass percentage of the positive electrode binder contained in the positive active electrode material layer may be 1 wt% to 20 wt%, such as 1 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, etc., preferably 1.2 wt% to 10 wt%.
[0085] The positive electrode also includes a positive electrode conductive material, which is mainly used to assist and improve the conductivity in the secondary battery, and there is no particular restriction on it in the embodiments of the present application, as long as it has conductivity without causing chemical changes. Specifically, the positive electrode conductive material may include graphite, such as natural graphite or artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; metal powders, such as fluorocarbon powders, aluminum powders and nickel powders; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives, and from the aspect of improving conductivity, the positive electrode conductive material may preferably be carbon black.
[0086] The specific surface area of the positive electrode conductive material can be 80m 2 / g~200m 2 / g, preferably 100m 2 / g~150m 2 / g.
[0087] The mass percentage of the positive electrode conductive material contained in the positive active electrode material layer may be 1 wt% to 20 wt%, for example, 1 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, etc., preferably 1.2 wt% to 10 wt%.
[0088] The thickness of the positive active electrode material layer may be 30 μm to 400 μm, for example, 30 μm, 40 μm, 50 μm, 80 μm, 110 μm, 200 μm, 300 μm, 400 μm, preferably 50 μm to 110 μm.
[0089] The positive electrode plate also includes a halide solid electrolyte, and the mass proportion of the halide solid electrolyte can be 1wt% to 50wt%, for example, 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, 30wt%, 40wt%, 50wt%, etc., preferably 10wt% to 20wt%.
[0090] In some embodiments, the positive electrode sheet can be prepared by a dry method, that is, the positive electrode active material, the positive electrode conductive material, the halide solid electrolyte, and the positive electrode binder are mixed. The positive electrode active material, the positive electrode conductive material, and the halide solid electrolyte can also be mixed first, and then the positive electrode binder is added. Under the action of high shear force, the binder is converted from a powder state to a fibrous state, and the positive electrode active material, the positive electrode conductive material, and the halide solid electrolyte are bonded together to form a positive active electrode material layer by rolling.
[0091] In some embodiments, the lithium-ion battery further includes a negative electrode plate, wherein a negative electrode tab is extended from the negative electrode plate.
[0092] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer formed on the surface of the negative electrode current collector, wherein the negative electrode active material layer at least comprises a negative electrode active material and a negative electrode binder.
[0093] There is no particular limitation on the negative electrode active material in the embodiments of the present application, as long as it is a material that can electrochemically absorb and release S-zone metal ions such as lithium ions, sodium ions, potassium ions, and magnesium ions, such as carbonaceous materials, metal compound materials, or their oxides, carbides, nitrides, silicides, sulfides, phosphides, etc. These materials can be used alone, or two or more of them can be used in combination.
[0094] In some embodiments, a carbon material can be selected as the negative electrode active material, and specifically one or more of the following can be selected: graphite, needle coke, amorphous carbon, a carbon-containing mesophase, carbon fiber, and a carbon material with a low degree of graphitization. Among them, graphite can include natural graphite, artificial graphite, etc. In addition, materials obtained by coating them with carbon materials, such as amorphous carbon and graphitized materials, can also be used. Amorphous carbon includes but is not limited to particles obtained by firing the entire mesophase, and particles obtained by infusible treatment and firing of a carbon precursor. As carbonaceous particles with a low degree of graphitization, particles obtained by firing organic matter at a temperature generally below 2500°C can be listed.
[0095] In addition, non-metallic materials that can be used as negative electrode active materials also include silicon and its compounds, such as Si, SiOx (0≤x<2). Since silicon-containing materials are prone to expansion, easy to fall off from the negative electrode current collector, and have poor conductivity, they are often mixed with carbon materials, such as core-shell structures containing carbon coating layers.
[0096] In some embodiments, metal elements and metal compounds can also be selected as negative electrode active materials, such as compounds containing metals or metalloids such as Li, Ag, Al, Bi, Cu, Ga, Ge, In, Ni, Pb, Sb, Si, Sn, Sr, and Zn.
[0097] The mass percentage of the negative electrode active material contained in the negative electrode active material layer may be 80 wt% to 99 wt%, for example, 80 wt%, 85 wt%, 90 wt%, 95 wt%, 97 wt%, 99 wt%, etc., preferably 95 wt% to 97 wt%.
[0098] When the negative electrode active material is a non-metallic material such as a carbon material, the negative electrode binder may be an aqueous binder such as one or more of sodium hydroxymethyl cellulose, styrene-butadiene latex, polyacrylic acid, acrylic copolymer, cyclodextrin, etc.;
[0099] The negative electrode active material layer can be obtained by coating the negative electrode slurry on the negative electrode current collector and then drying it. The negative electrode slurry includes at least the negative electrode active material and the negative electrode binder. When an aqueous solvent is used as the liquid medium for forming the negative electrode slurry, it is preferred to use a thickener for slurrying. The thickener can generally be used to adjust the viscosity of the slurry.
[0100] The thickener in the embodiment of the present application can be one or more of the following: carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein and their salts, etc.
[0101] The mass proportion of the thickener in the negative electrode slurry can be 0.1wt% to 5wt%, for example, 0.1wt%, 0.2wt%, 0.5wt%, 0.6wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, etc., preferably 0.5wt% to 3wt%, and more preferably 0.6wt% to 2wt%.
[0102] It should be noted that in the embodiments of the present application, the positive active electrode material layer and / or the negative active material layer may also be dry pressed without using a binder, and there is no limitation here, and the user may set it according to actual needs.
[0103] The present application will be further described below with reference to specific embodiments and comparative examples.
[0104] Example 1
[0105] The present embodiment provides a polymer-based composite solid electrolyte membrane, comprising a plurality of stacked solid electrolyte layers, each of which comprises a halide solid electrolyte and a polymer solid electrolyte. The halide solid electrolyte comprises Li 3 InCl 6 The polymer solid electrolyte includes a first polymer solid electrolyte PEO (polyethylene oxide), wherein the polymer-based composite solid electrolyte membrane includes two solid electrolyte layers, in which the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is 80:20 in the solid electrolyte layer close to the positive electrode side; in the solid electrolyte layer close to the negative electrode side, the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is 20:80. In the solid electrolyte layer close to the positive electrode side and the solid electrolyte layer close to the negative electrode side, the halide solid electrolyte is Li 3 InCl 6 The polymer solid electrolyte includes a first polymer solid electrolyte PEO. The polymer solid electrolyte also includes a lithium salt. In this embodiment, the lithium salt is lithium bis(trifluoromethanesulfonyl imide), and the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95.
[0106] In this embodiment, the solid electrolyte layer further includes a binder, and the binder is polytetrafluoroethylene (PTFE). The mass proportion of the binder in the solid electrolyte layer is 2 wt %.
[0107] This embodiment provides a method for preparing a polymer-based composite solid electrolyte membrane, comprising the following steps:
[0108] S1. Prepare separate solid electrolyte layers:
[0109] S11, weigh the halide solid electrolyte Li according to the mass ratio of 80:20 3 InCl 6 , polymer solid electrolyte. The polymer electrolyte includes a first polymer solid electrolyte PEO and a lithium salt of lithium bis(trifluoromethanesulfonyl imide), wherein the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95. Weigh the binder PTFE, which accounts for 2wt% of the mass of the entire solid electrolyte layer, mix it with a jet mill, and then shear the mixture with a high-speed shearing machine at a speed of 25,000 r / min for 10 minutes to complete the fiberization process of the binder, and then roll-form it on a roller device at a temperature of 120°C to prepare a solid electrolyte layer close to the positive electrode side;
[0110] S12, weigh the halide solid electrolyte Li according to the mass ratio of 20:80 3 InCl 6, polymer solid electrolyte. The polymer electrolyte includes PEO and lithium salt lithium bis(trifluoromethanesulfonyl imide), wherein the mass ratio of lithium salt to polymer solid electrolyte is 5:95. Weigh the binder PTFE, which accounts for 2wt% of the mass of the whole solid electrolyte layer, mix it through a jet mill, and then shear the mixture through a high-speed shearing machine at a speed of 25000r / min for 10min to complete the fiberization process of the binder, and then roll-form it on a roller equipment at a temperature of 120°C to prepare a solid electrolyte layer close to the negative electrode side;
[0111] S2. Align and stack the solid electrolyte layer close to the positive electrode side and the solid electrolyte layer close to the negative electrode side, and roll them together through a double-roll device to prepare a polymer-based composite solid electrolyte membrane.
[0112] This embodiment provides a lithium battery, including a positive electrode, a negative electrode, and a polymer-based composite solid electrolyte membrane prepared as described above disposed between the positive and negative electrodes;
[0113] The positive electrode includes a positive electrode active material, and the positive electrode active material includes a high voltage positive electrode material. In this embodiment, the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 ; The negative electrode includes a negative electrode active material. In this embodiment, the negative electrode active material is graphite.
[0114] Example 2
[0115] This embodiment provides a polymer-based composite solid electrolyte membrane, including a plurality of stacked solid electrolyte layers, wherein the solid electrolyte layers each include a halide solid electrolyte and a polymer solid electrolyte, wherein the halide solid electrolyte includes Li 3 InCl 6 The polymer solid electrolyte includes a first polymer solid electrolyte PEO (polyethylene oxide), wherein the polymer-based composite solid electrolyte membrane includes three solid electrolyte layers, in the solid electrolyte layer close to the positive electrode side, the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is 80:20; in the solid electrolyte layer close to the negative electrode side, the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is 20:80. In the solid electrolyte layer between the two, the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is 50:50. In the three solid electrolyte layers, the halide solid electrolytes are all Li 3 InCl 6The polymer solid electrolyte includes a first polymer solid electrolyte PEO. The polymer solid electrolyte also includes a lithium salt. In this embodiment, the lithium salt is lithium bis(trifluoromethanesulfonyl imide), and the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95.
[0116] In this embodiment, the solid electrolyte layer further includes a binder, and the binder is polytetrafluoroethylene (PTFE). The mass proportion of the binder in the solid electrolyte layer is 2 wt %.
[0117] This embodiment provides a method for preparing a polymer-based composite solid electrolyte membrane, comprising the following steps:
[0118] S1. Prepare separate solid electrolyte layers:
[0119] S11, weigh the halide solid electrolyte Li according to the mass ratio of 80:20 3 InCl 6 , polymer solid electrolyte. The polymer electrolyte includes a first polymer solid electrolyte PEO and a lithium salt of lithium bis(trifluoromethanesulfonyl imide), wherein the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95. Weigh the binder PTFE, which accounts for 2wt% of the mass of the entire solid electrolyte layer, mix it with a jet mill, and then shear the mixture with a high-speed shearing machine at a speed of 25,000 r / min for 10 minutes to complete the fiberization process of the binder, and then roll-form it on a roller device at a temperature of 120°C to prepare a solid electrolyte layer close to the positive electrode side;
[0120] S12, weigh the halide solid electrolyte Li according to the mass ratio of 20:80 3 InCl 6 , polymer solid electrolyte. The polymer electrolyte includes a first polymer solid electrolyte PEO and a lithium salt of lithium bis(trifluoromethanesulfonyl imide), wherein the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95. Weigh the binder PTFE, which accounts for 2wt% of the mass of the entire solid electrolyte layer, mix it with a jet mill, and then shear the mixture with a high-speed shearing machine at a speed of 25,000 r / min for 10 minutes to complete the fiberization process of the binder, and then roll-form it on a roller device at a temperature of 120°C to prepare a solid electrolyte layer close to the negative electrode side;
[0121] S13, weigh the halide solid electrolyte Li according to the mass ratio of 50:50 3 InCl 6, polymer solid electrolyte. The polymer electrolyte includes a first polymer solid electrolyte PEO and a lithium salt of lithium bis(trifluoromethanesulfonyl imide), wherein the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95. Weigh the binder PTFE, which accounts for 2wt% of the mass of the entire solid electrolyte layer, mix it with a jet mill, and then shear the mixture with a high-speed shearing machine at a speed of 25,000 r / min for 10 minutes to complete the fiberization process of the binder, and then roll-form it on a roller device at a temperature of 120°C to prepare a solid electrolyte layer located in the middle;
[0122] S2. Align and stack the solid electrolyte layer close to the positive electrode, the middle solid electrolyte layer and the solid electrolyte layer close to the negative electrode, and roll them together through a double-roll device to prepare a polymer-based composite solid electrolyte membrane.
[0123] This embodiment provides a lithium battery, including a positive electrode, a negative electrode, and a polymer-based composite solid electrolyte membrane prepared as described above disposed between the positive and negative electrodes;
[0124] The positive electrode includes a positive electrode active material, and the positive electrode active material includes a high voltage positive electrode material. In this embodiment, the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 ; The negative electrode includes a negative electrode active material. In this embodiment, the negative electrode active material is graphite.
[0125] Example 3
[0126] This embodiment provides a polymer-based composite solid electrolyte membrane, including a plurality of stacked solid electrolyte layers, wherein the solid electrolyte layers each include a halide solid electrolyte and a polymer solid electrolyte, wherein the halide solid electrolyte includes Li 3 InCl 6 , the polymer solid electrolyte includes a first polymer solid electrolyte PEO (polyethylene oxide), wherein the polymer-based composite solid electrolyte membrane includes 6 solid electrolyte layers, in the solid electrolyte layer closest to the positive electrode side, the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is 80:20; in the solid electrolyte layer closest to the negative electrode side, the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is 20:80. In the solid electrolyte layer between the two, the mass ratios of the halide solid electrolyte to the polymer solid electrolyte are 68:32, 56:44, 44:56, and 32:68 from the positive electrode side to the negative electrode side, respectively. In the 6 solid electrolyte layers, the halide solid electrolytes are all Li 3 InCl 6The polymer solid electrolyte includes a first polymer solid electrolyte PEO. The polymer solid electrolyte also includes a lithium salt. In this embodiment, the lithium salt is lithium bis(trifluoromethanesulfonyl imide), and the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95.
[0127] In this embodiment, the solid electrolyte layer further includes a binder, and the binder is polytetrafluoroethylene (PTFE). The mass proportion of the binder in the solid electrolyte layer is 2 wt %.
[0128] This embodiment provides a method for preparing a polymer-based composite solid electrolyte membrane, comprising the following steps:
[0129] S1. Prepare separate solid electrolyte layers:
[0130] S11, weigh the halide solid electrolyte Li according to the mass ratio of 80:20 3 InCl 6 , polymer solid electrolyte. The polymer electrolyte includes a first polymer solid electrolyte PEO and a lithium salt of lithium bis(trifluoromethanesulfonyl imide), wherein the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95. Weigh the binder PTFE, which accounts for 2wt% of the mass of the entire solid electrolyte layer, mix it with a jet mill, and then shear the mixture with a high-speed shearing machine at a speed of 25,000 r / min for 10 minutes to complete the fiberization process of the binder, and then roll-form it on a roller device at a temperature of 120°C to prepare a solid electrolyte layer close to the positive electrode side;
[0131] S12, weigh the halide solid electrolyte Li according to the mass ratio of 20:80 3 InCl 6 , polymer solid electrolyte. The polymer electrolyte includes a first polymer solid electrolyte PEO and a lithium salt of lithium bis(trifluoromethanesulfonyl imide), wherein the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95. Weigh the binder PTFE, which accounts for 2wt% of the mass of the entire solid electrolyte layer, mix it with a jet mill, and then shear the mixture with a high-speed shearing machine at a speed of 25,000 r / min for 10 minutes to complete the fiberization process of the binder, and then roll-form it on a roller device at a temperature of 120°C to prepare a solid electrolyte layer close to the negative electrode side;
[0132] S13, weigh the halide solid electrolyte Li according to the mass ratio of 68:32. 3 InCl 6, polymer solid electrolyte. The polymer electrolyte includes a first polymer solid electrolyte PEO and a lithium salt of lithium bis(trifluoromethanesulfonyl imide), wherein the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95. Weigh the binder PTFE, which accounts for 2wt% of the mass of the entire solid electrolyte layer, mix it with a jet mill, and then shear the mixture with a high-speed shearing machine at a speed of 25,000 r / min for 10 minutes to complete the fiberization process of the binder, and then roll-form it on a roller equipment at a temperature of 120°C to prepare a solid electrolyte layer;
[0133] S14, weigh the halide solid electrolyte Li according to the mass ratio of 56:44. 3 InCl 6 , polymer solid electrolyte. The polymer electrolyte includes a first polymer solid electrolyte PEO and a lithium salt of lithium bis(trifluoromethanesulfonyl imide), wherein the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95. Weigh the binder PTFE, which accounts for 2wt% of the mass of the entire solid electrolyte layer, mix it with a jet mill, and then shear the mixture with a high-speed shearing machine at a speed of 25,000 r / min for 10 minutes to complete the fiberization process of the binder, and then roll-form it on a roller equipment at a temperature of 120°C to prepare a solid electrolyte layer;
[0134] S15, weigh the halide solid electrolyte Li according to the mass ratio of 44:56 3 InCl 6 , polymer solid electrolyte. The polymer electrolyte includes a first polymer solid electrolyte PEO and a lithium salt of lithium bis(trifluoromethanesulfonyl imide), wherein the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95. Weigh the binder PTFE, which accounts for 2wt% of the mass of the entire solid electrolyte layer, mix it with a jet mill, and then shear the mixture with a high-speed shearing machine at a speed of 25,000 r / min for 10 minutes to complete the fiberization process of the binder, and then roll-form it on a roller equipment at a temperature of 120°C to prepare a solid electrolyte layer;
[0135] S15, weigh the halide solid electrolyte Li according to the mass ratio of 32:68 3 InCl 6, polymer solid electrolyte. The polymer electrolyte includes a first polymer solid electrolyte PEO and a lithium salt of lithium bis(trifluoromethanesulfonyl imide), wherein the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95. Weigh the binder PTFE, which accounts for 2wt% of the mass of the entire solid electrolyte layer, mix it with a jet mill, and then shear the mixture with a high-speed shearing machine at a speed of 25,000 r / min for 10 minutes to complete the fiberization process of the binder, and then roll-form it on a roller equipment at a temperature of 120°C to prepare a solid electrolyte layer;
[0136] S2. Align and stack the above-mentioned solid electrolyte layers in ascending order according to the mass proportion of the halide solid electrolyte, and roll-compound them by a double-roll device to prepare a polymer-based composite solid electrolyte membrane.
[0137] This embodiment provides a lithium battery, including a positive electrode, a negative electrode, and a polymer-based composite solid electrolyte membrane prepared as described above disposed between the positive and negative electrodes;
[0138] The positive electrode includes a positive electrode active material, and the positive electrode active material includes a high voltage positive electrode material. In this embodiment, the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 ; The negative electrode includes a negative electrode active material. In this embodiment, the negative electrode active material is graphite.
[0139] Example 4
[0140] This embodiment provides a polymer-based composite solid electrolyte membrane, including a plurality of stacked solid electrolyte layers, wherein the solid electrolyte layers each include a halide solid electrolyte and a polymer solid electrolyte, wherein the halide solid electrolyte includes Li 3 InCl 6 The polymer solid electrolyte includes a first polymer solid electrolyte PEO (polyethylene oxide), wherein the polymer-based composite solid electrolyte membrane includes two solid electrolyte layers, in which the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is 70:30 in the solid electrolyte layer close to the positive electrode side; in the solid electrolyte layer close to the negative electrode side, the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is 30:70. In the solid electrolyte layer close to the positive electrode side and the solid electrolyte layer close to the negative electrode side, the halide solid electrolyte is Li 3 InCl 6 The polymer solid electrolyte includes a first polymer solid electrolyte PEO. The polymer solid electrolyte also includes a lithium salt. In this embodiment, the lithium salt is lithium bis(trifluoromethanesulfonyl imide), and the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95.
[0141] In this embodiment, the solid electrolyte layer further includes a binder, and the binder is polytetrafluoroethylene (PTFE). The mass proportion of the binder in the solid electrolyte layer is 2 wt %.
[0142] This embodiment provides a method for preparing a polymer-based composite solid electrolyte membrane, comprising the following steps:
[0143] S1. Prepare separate solid electrolyte layers:
[0144] S11, weigh the halide solid electrolyte Li according to the mass ratio of 70:30 3 InCl 6 , polymer solid electrolyte. The polymer electrolyte includes a first polymer solid electrolyte PEO and a lithium salt of lithium bis(trifluoromethanesulfonyl imide), wherein the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95. Weigh the binder PTFE, which accounts for 2wt% of the mass of the entire solid electrolyte layer, mix it with a jet mill, and then shear the mixture with a high-speed shearing machine at a speed of 25,000 r / min for 10 minutes to complete the fiberization process of the binder, and then roll-form it on a roller device at a temperature of 120°C to prepare a solid electrolyte layer close to the positive electrode side;
[0145] S12, weigh the halide solid electrolyte Li according to the mass ratio of 30:70 3 InCl 6 , polymer solid electrolyte. The polymer electrolyte includes a first polymer solid electrolyte PEO and a lithium salt of lithium bis(trifluoromethanesulfonyl imide), wherein the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95. Weigh the binder PTFE, which accounts for 2wt% of the mass of the entire solid electrolyte layer, mix it with a jet mill, and then shear the mixture with a high-speed shearing machine at a speed of 25,000 r / min for 10 minutes to complete the fiberization process of the binder, and then roll-form it on a roller device at a temperature of 120°C to prepare a solid electrolyte layer close to the negative electrode side;
[0146] S2. Align and stack the solid electrolyte layer close to the positive electrode side and the solid electrolyte layer close to the negative electrode side, and roll them together through a double-roll device to prepare a polymer-based composite solid electrolyte membrane.
[0147] This embodiment provides a lithium battery, including a positive electrode, a negative electrode, and a polymer-based composite solid electrolyte membrane prepared as described above disposed between the positive and negative electrodes;
[0148] The positive electrode includes a positive electrode active material, and the positive electrode active material includes a high voltage positive electrode material. In this embodiment, the positive electrode active material is LiNi 0.8Co 0.1 Mn 0.1 O 2 ; The negative electrode includes a negative electrode active material. In this embodiment, the negative electrode active material is graphite.
[0149] Example 5
[0150] This embodiment provides a polymer-based composite solid electrolyte membrane, including a plurality of stacked solid electrolyte layers, wherein the solid electrolyte layers each include a halide solid electrolyte and a polymer solid electrolyte, wherein the halide solid electrolyte includes Li 3 InCl 6 The polymer solid electrolyte includes a first polymer solid electrolyte PEO (polyethylene oxide), wherein the polymer-based composite solid electrolyte membrane includes two solid electrolyte layers, in which the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is 50:50 in the solid electrolyte layer close to the positive electrode side; in the solid electrolyte layer close to the negative electrode side, the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is 20:80. In the solid electrolyte layer close to the positive electrode side and the solid electrolyte layer close to the negative electrode side, the halide solid electrolyte is Li 3 InCl 6 The polymer solid electrolyte includes a first polymer solid electrolyte PEO. The polymer solid electrolyte also includes a lithium salt. In this embodiment, the lithium salt is lithium bis(trifluoromethanesulfonyl imide), and the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95.
[0151] In this embodiment, the solid electrolyte layer further includes a binder, and the binder is polytetrafluoroethylene (PTFE). The mass proportion of the binder in the solid electrolyte layer is 2 wt %.
[0152] This embodiment provides a method for preparing a polymer-based composite solid electrolyte membrane, comprising the following steps:
[0153] S1. Prepare separate solid electrolyte layers:
[0154] S11, weigh the halide solid electrolyte Li according to the mass ratio of 50:50 3 InCl 6, polymer solid electrolyte. The polymer electrolyte includes a first polymer solid electrolyte PEO and a lithium salt of lithium bis(trifluoromethanesulfonyl imide), wherein the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95. Weigh the binder PTFE, which accounts for 2wt% of the mass of the entire solid electrolyte layer, mix it with a jet mill, and then shear the mixture with a high-speed shearing machine at a speed of 25,000 r / min for 10 minutes to complete the fiberization process of the binder, and then roll-form it on a roller device at a temperature of 120°C to prepare a solid electrolyte layer close to the positive electrode side;
[0155] S12, weigh the halide solid electrolyte Li according to the mass ratio of 20:80 3 InCl 6 , polymer solid electrolyte. The polymer electrolyte includes a first polymer solid electrolyte PEO and a lithium salt of lithium bis(trifluoromethanesulfonyl imide), wherein the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95. Weigh the binder PTFE, which accounts for 2wt% of the mass of the entire solid electrolyte layer, mix it with a jet mill, and then shear the mixture with a high-speed shearing machine at a speed of 25,000 r / min for 10 minutes to complete the fiberization process of the binder, and then roll-form it on a roller device at a temperature of 120°C to prepare a solid electrolyte layer close to the negative electrode side;
[0156] S2. Align and stack the solid electrolyte layer close to the positive electrode side and the solid electrolyte layer close to the negative electrode side, and roll them together through a double-roll device to prepare a polymer-based composite solid electrolyte membrane.
[0157] This embodiment provides a lithium battery, including a positive electrode, a negative electrode, and a polymer-based composite solid electrolyte membrane prepared as described above disposed between the positive and negative electrodes;
[0158] The positive electrode includes a positive electrode active material, and the positive electrode active material includes a high voltage positive electrode material. In this embodiment, the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 ; The negative electrode includes a negative electrode active material. In this embodiment, the negative electrode active material is graphite.
[0159] Example 6
[0160] This embodiment provides a polymer-based composite solid electrolyte membrane, including a plurality of stacked solid electrolyte layers, wherein the solid electrolyte layers each include a halide solid electrolyte and a polymer solid electrolyte, wherein the halide solid electrolyte includes Li 3 InCl 6The polymer solid electrolyte includes a first polymer solid electrolyte PEO (polyethylene oxide), wherein the polymer-based composite solid electrolyte membrane includes two solid electrolyte layers, in which the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is 90:10 in the solid electrolyte layer close to the positive electrode side; in the solid electrolyte layer close to the negative electrode side, the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is 10:90. In the solid electrolyte layer close to the positive electrode side and the solid electrolyte layer close to the negative electrode side, the halide solid electrolyte is Li 3 InCl 6 The polymer solid electrolyte includes a first polymer solid electrolyte PEO. The polymer solid electrolyte also includes a lithium salt. In this embodiment, the lithium salt is lithium bis(trifluoromethanesulfonyl imide), and the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95.
[0161] In this embodiment, the solid electrolyte layer further includes a binder, and the binder is polytetrafluoroethylene (PTFE). The mass proportion of the binder in the solid electrolyte layer is 2 wt %.
[0162] This embodiment provides a method for preparing a polymer-based composite solid electrolyte membrane, comprising the following steps:
[0163] S1. Prepare separate solid electrolyte layers:
[0164] S11, weigh the halide solid electrolyte Li according to the mass ratio of 90:10 3 InCl 6 , polymer solid electrolyte. The polymer electrolyte includes a first polymer solid electrolyte PEO and a lithium salt of lithium bis(trifluoromethanesulfonyl imide), wherein the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95. Weigh the binder PTFE, which accounts for 2wt% of the mass of the entire solid electrolyte layer, mix it with a jet mill, and then shear the mixture with a high-speed shearing machine at a speed of 25,000 r / min for 10 minutes to complete the fiberization process of the binder, and then roll-form it on a roller device at a temperature of 120°C to prepare a solid electrolyte layer close to the positive electrode side;
[0165] S12, weigh the halide solid electrolyte Li according to the mass ratio of 10:90 3 InCl 6, polymer solid electrolyte. The polymer electrolyte includes PEO and lithium salt lithium bis(trifluoromethanesulfonyl imide), wherein the mass ratio of lithium salt to polymer solid electrolyte is 5:95. Weigh the binder PTFE, which accounts for 2wt% of the mass of the whole solid electrolyte layer, mix it through a jet mill, and then shear the mixture through a high-speed shearing machine at a speed of 25000r / min for 10min to complete the fiberization process of the binder, and then roll-form it on a roller equipment at a temperature of 120°C to prepare a solid electrolyte layer close to the negative electrode side;
[0166] S2. Align and stack the solid electrolyte layer close to the positive electrode side and the solid electrolyte layer close to the negative electrode side, and roll them together through a double-roll device to prepare a polymer-based composite solid electrolyte membrane.
[0167] This embodiment provides a lithium battery, including a positive electrode, a negative electrode, and a polymer-based composite solid electrolyte membrane prepared as described above disposed between the positive and negative electrodes;
[0168] The positive electrode includes a positive electrode active material, and the positive electrode active material includes a high voltage positive electrode material. In this embodiment, the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 ; The negative electrode includes a negative electrode active material. In this embodiment, the negative electrode active material is graphite.
[0169] Example 7
[0170] This embodiment provides a polymer-based composite solid electrolyte membrane, including a plurality of stacked solid electrolyte layers, wherein the solid electrolyte layers each include a halide solid electrolyte and a polymer solid electrolyte, wherein the halide solid electrolyte includes Li 3 YC 3 Br 3 The polymer solid electrolyte includes a first polymer solid electrolyte PMMA (polymethyl methacrylate), wherein the polymer-based composite solid electrolyte membrane includes two solid electrolyte layers, in which the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is 80:20 in the solid electrolyte layer close to the positive electrode side; in the solid electrolyte layer close to the negative electrode side, the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is 20:80. In the solid electrolyte layer close to the positive electrode side and the solid electrolyte layer close to the negative electrode side, the halide solid electrolyte is Li 3 YC 3 Br 3The polymer solid electrolyte includes a first polymer solid electrolyte PMMA. The polymer solid electrolyte also includes a lithium salt. In this embodiment, the lithium salt is lithium hexafluorophosphate, and the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95.
[0171] This embodiment provides a method for preparing a polymer-based composite solid electrolyte membrane, comprising the following steps:
[0172] S1. Prepare separate solid electrolyte layers:
[0173] S11, weigh the halide solid electrolyte Li according to the mass ratio of 80:20 3 YC 3 Br 3 , polymer solid electrolyte. The polymer electrolyte includes a first polymer solid electrolyte PMMA and a lithium salt lithium hexafluorophosphate, wherein the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95. The mixture is mixed by a jet mill and then pressed in a mold at a temperature of 120°C to prepare a solid electrolyte layer close to the positive electrode side;
[0174] S12, weigh the halide solid electrolyte Li according to the mass ratio of 20:80 3 YC 3 Br 3 , polymer solid electrolyte. The polymer electrolyte includes a first polymer solid electrolyte PMMA and a lithium salt lithium hexafluorophosphate, wherein the mass ratio of the lithium salt to the first polymer solid electrolyte is 5:95. The mixture is mixed by a jet mill and then pressed in a mold at a temperature of 120°C to prepare a solid electrolyte layer close to the negative electrode side;
[0175] S2. Align and stack the solid electrolyte layer close to the positive electrode side and the solid electrolyte layer close to the negative electrode side, and roll them together through a double-roll device to prepare a polymer-based composite solid electrolyte membrane.
[0176] This embodiment provides a lithium battery, including a positive electrode, a negative electrode, and a polymer-based composite solid electrolyte membrane prepared as described above disposed between the positive and negative electrodes;
[0177] The positive electrode includes a positive electrode active material, and the positive electrode active material includes a high voltage positive electrode material. In this embodiment, the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 ; The negative electrode includes a negative electrode active material. In this embodiment, the negative electrode active material is graphite.
[0178] Comparative Example 1
[0179] The difference between this comparative example and Example 1 is that no polymer electrolyte is provided in the solid electrolyte layer close to the positive electrode side and no halide solid electrolyte is provided in the solid electrolyte layer close to the negative electrode side, and the other technical features are the same.
[0180] Comparative Example 2
[0181] The difference between this comparative example and Example 1 is that the composite solid electrolyte membrane includes a halide solid electrolyte layer, the halide solid electrolyte layer includes a halide solid electrolyte and a binder, and the mass ratio of the two is 98:2, and the other technical features are the same.
[0182] Comparative Example 3
[0183] The difference between this comparative example and Example 1 is that the composite solid electrolyte membrane includes a polymer solid electrolyte layer, and the other technical features are the same.
[0184] Comparative Example 4
[0185] The difference between this comparative example and Example 1 is that the polymer solid electrolyte in the solid electrolyte layer is replaced by pure PVDF without ion transport performance, and the solid electrolyte layer does not include a fiberized binder, and the other technical features are the same.
[0186] Test method:
[0187] 1) Ionic conductivity
[0188] The ionic conductivity of the solid electrolyte membrane was obtained by assembling a symmetrical cell with a steel sheet as the blocking electrode and measuring the electrochemical impedance spectroscopy on an electrochemical workstation at a frequency range of 0.1 Hz to 7 MHz, an amplitude of 10 mV, and a temperature of 25° C. The results are shown in Table 1 below.
[0189] 2) Porosity
[0190] Solid electrolyte membranes were prepared according to the ratios of the examples and comparative examples and cut into 1 cm 2 The size of each solid electrolyte membrane is measured, and the weight and volume of each solid electrolyte membrane are measured (the apparent density is measured), and the apparent density is compared with the designed value (true density) to calculate the porosity. In other words, the true density of each solid electrolyte membrane is calculated from the composition ratio of the components contained in each solid electrolyte membrane and the density of each component, and then the porosity is calculated from the difference between the apparent density and the true density.
[0191] 3) Discharge capacity
[0192] The lithium-ion batteries prepared in the above embodiments and comparative examples were subjected to cycle tests. At a temperature of 25°C±2°C, the first step was to charge at 0.1C or a specified current to a final voltage (4.3V), a cutoff current of 0.01C, and stand for 30 minutes; the second step was to discharge at 0.1C to a final discharge voltage (2.75V), record the discharge capacity, and stand for 30 minutes; the first and second steps were repeated to test the cycle performance of the battery for 300 cycles. The test results are shown in Table 1 below.
[0193] 4) Cycle performance
[0194] The lithium-ion batteries prepared in the above embodiments and comparative examples were subjected to cycle tests. At a temperature of 25°C±2°C, the first step was to charge at 1C or a specified current to a final voltage (4.3V), a cutoff current of 0.05C, and stand for 30 minutes; the second step was to discharge at 1C to a final discharge voltage (2.75V), record the discharge capacity, and stand for 30 minutes; the first and second steps were cycled to test the cycle performance of the battery for 300 cycles. The test results are shown in Table 1 below.
[0195] Table 1
[0196]
[0197]
[0198] As can be seen from Table 1, by comparing Comparative Example 1 with Example 1, compared with the composite electrolyte membrane formed by forming a single halide solid electrolyte layer and a single polymer solid electrolyte layer, the polymer-based composite solid electrolyte membrane of the present application has higher ion conductivity, smaller internal resistance of the battery, and better capacity and cycle performance of the battery. The possible reason is that there is no interface effect or smaller interface resistance between the solid electrolyte layers in the present application, and the halide solid electrolyte with higher ion conductivity forms a continuous lithium ion transmission channel from the positive electrode to the negative electrode, and the combination of the polymer electrolyte and the lithium salt provides an additional lithium ion transmission channel. The above is only a possible speculation on the mechanism of the technical solution of the present application, and does not constitute a limitation on the scope of protection of the present application.
[0199] By comparing Comparative Example 2 with Example 1, it can be seen that the polymer-based composite solid electrolyte membrane prepared in the present application has a higher density. The possible reason is that, during rolling, since the polymer solid electrolyte has a certain elasticity, it is beneficial for the polymer solid electrolyte to fill the pores formed by the halide solid electrolyte particles, which is beneficial to improve the density of the composite electrolyte membrane. Moreover, compared with the battery prepared by the solid electrolyte membrane formed by a simple halide solid electrolyte, the cycle retention rate of the battery of the present application is more excellent. The possible reason is that the simple halide solid electrolyte has poor compatibility with the negative electrode, and the synergistic effect of the halide solid electrolyte and the polymer solid electrolyte can effectively solve this problem.
[0200] By comparing Comparative Example 3 with Example 1, it can be seen that compared with the battery prepared by the solid electrolyte membrane formed by a simple polymer solid electrolyte, the discharge capacity of the battery of the present application is more excellent.
[0201] From the comparison between Comparative Example 4 and Example 1, it can be seen that when a polymer without lithium ion transmission efficiency exists in a solid electrolyte, it will affect the lithium ion transmission efficiency of the polymer-based composite solid electrolyte membrane, resulting in a lower discharge capacity of the battery.
[0202] It can be seen that the present application prepares a polymer-based composite solid electrolyte membrane composed of several solid electrolyte layers with different mass proportions of halide solid electrolytes, which has good high-voltage resistance, good negative electrode compatibility, and good ionic conductivity. By arranging the mass ratio of halide solid electrolyte to polymer solid electrolyte in the solid electrolyte layer from the positive electrode side to the negative electrode side, it can achieve excellent compatibility with the positive and negative electrodes at the same time, which can effectively improve the capacity performance of the battery and the cycle performance of the battery.
[0203] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0204] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A polymer-based composite solid electrolyte membrane, characterized in that: The composite solid electrolyte membrane comprises N solid electrolyte layers, each of which comprises a halide solid electrolyte and a polymer solid electrolyte, and the outermost solid electrolyte layer is the first solid electrolyte layer and the Nth solid electrolyte layer, then: The mass proportion of the halide solid electrolyte in the first solid electrolyte layer is greater than the mass proportion of the halide solid electrolyte in the Nth solid electrolyte layer; The types of the halide solid electrolytes in different solid electrolyte layers are the same or different.
2. The polymer-based composite solid electrolyte membrane according to claim 1, characterized in that: The N solid electrolyte layers are stacked and satisfy that the mass ratio of the halide solid electrolyte to the polymer solid electrolyte in each solid electrolyte layer gradually decreases from the first solid electrolyte layer to the Nth solid electrolyte layer.
3. The polymer-based composite solid electrolyte membrane according to claim 1, characterized in that: In each of the solid electrolyte layers, the mass ratio of the halide solid electrolyte to the polymer solid electrolyte is (90:10) to (5:95).
4. The polymer-based composite solid electrolyte membrane according to claim 1, characterized in that: In the first solid electrolyte layer, the mass proportion of the halide solid electrolyte is 50wt% to 90wt%; Preferably, in the Nth solid electrolyte layer, the mass proportion of the polymer solid electrolyte is 70wt% to 95wt%.
5. The polymer-based composite solid electrolyte membrane according to claim 1, characterized in that: The halide solid electrolyte includes Li a M b X6, wherein M includes one or more combinations of Zr, Hf, In, Sc, Y, La, Ce, Pr, Nb, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; X includes a halogen element or a combination of a halogen element and an O element or a combination of a halogen element and an S element, and the halogen element includes one or more combinations of F, Cl, Br, and I; a>0, b>0, and a+b=6.
6. The polymer-based composite solid electrolyte membrane according to claim 1, characterized in that: The polymer solid electrolyte includes a first polymer solid electrolyte, and the first polymer solid electrolyte includes one or more of PEO, PVDF, PMMA, PAN, PVC, PA, PEGDA, and PTMC; Preferably, the first polymer solid electrolyte comprises PEO.
7. The polymer-based composite solid electrolyte membrane according to claim 1, characterized in that: The halide solid electrolytes in the N solid electrolyte layers are of the same type, and the polymer solid electrolytes are of the same type.
8. The polymer-based composite solid electrolyte membrane according to claim 6, characterized in that: The polymer solid electrolyte also includes a lithium salt; Preferably, in the polymer solid electrolyte, the mass ratio of the lithium salt to the first polymer solid electrolyte is (5:95) to (60:40).
9. A method for preparing a polymer-based composite solid electrolyte membrane as claimed in claim 1, characterized in that: The steps include: S1. Prepare separate solid electrolyte layers: weigh raw materials, mix and press to form solid electrolyte layers; S2. Composite: Roll-compound the N solid electrolyte layers prepared in step S1.
10. A lithium battery, characterized in that: A polymer-based composite solid electrolyte membrane according to claim 1, comprising a positive electrode, a negative electrode and a polymer-based composite solid electrolyte membrane disposed between the positive and negative electrodes; The first solid electrolyte layer is in contact with the positive electrode, and the Nth solid electrolyte layer is in contact with the negative electrode. The positive electrode includes a positive electrode active material, and the positive electrode active material includes a high voltage positive electrode material.
Citation Information
Cited By
Solid-state lithium battery polymer electrolyte and preparation method thereof
CN120545444B
Multilayer composite electrolyte membrane and preparation method thereof
CN121282323A
Double-layer composite solid electrolyte membrane, preparation method thereof and all-solid-state lithium battery
CN121439882A